Understanding the effect of sodium polyphosphate on improving the chemical stability of Ti3C2Tz MXene in water - Huang, Shuohan; Natu, Varun; Tao, Jingyi; Xia, Yumin; Mochalin, Vadym N.; Barsoum, Michel W. (Journal of Materials Chemistry A, 2022)
Degradation of MXenes in aqueous environments severely limits the application and industrialization of this large family of two-dimensional (2D) materials. Hydrolysis and oxidation are now considered as two main degradation mechanisms and while significant efforts have been directed to prolonging the shelf-life of MXenes, separating and studying their degradation mechanisms have lagged behind. Herein, gas analysis via gas chromatography and Raman spectroscopy were used to investigate the effect of sodium polyphosphate, PP, on the degradation of Ti3C2Tz MXene. Transmission and scanning electron microscopies, as well as X-ray photoelectron spectroscopywere also used as complimentary techniques to support conclusions derived from gas analysis and to confirm the extent of degradation via characterization of solid reaction products. Based on these studies we have determined that the addition of PP to an equal mass of Ti3C2Tz solution can effectively suppress hydrolysis and protect Ti3C2Tz from degradation.

MXene surface terminations: a perspective - Natu, Varun; Barsoum, Michel W. (Journal of Physical Chemistry C, 2023)
Two-dimensional (2D) transition metal carbides and nitrides are among the newest, and probably largest, families of 2D materials that have been discovered. They have shown promise in many applications, such as electromagnetic shielding, energy storage devices like batteries and supercapacitors, transparent conductive electrodes, as catalysts for hydrogen production, and several others. Their general formula is Mn+1XnTz (n = 1-4) or M1.33XTz, where M is an early transition metal, X is carbon and/or nitrogen, and T-z represents various terminations present upon etching the Al layer. The first MXene discovered, Ti3C2Tz, was synthesized by etching aluminum (Al) from the nanolaminated MAX phase Ti3AlC2 using hydrofluoric acid (HF). Since the discovery of Ti3C2Tz in 2011, more than 30 other MXene chemistries have been reported with different M and X elements. It has been observed that, as expected, changing the MXene chemistry also influences the properties in the range of applications listed above, allowing us to tailor them according to what suits the application of interest the best. Unlike the success in tailoring the M and X elements over the years, attempts to engineer T-z was, until recently, a challenge. A series of recent discoveries and an improved understanding of MXene surface properties has now rendered the customization of T-z possible. This progress added a new ``knob'' that can be turned to further tune MXene properties. The majority of this Perspective is focused on surface terminations: their engineering, characterization, and effect on MXene properties.

Non-confined gamma monoclinic sulfur cathode in carbonate electrolyte based room temperature K-S batteries - Pai, Rahul; Cardoza, Neal Amadeus; Natu, Varun; Barsoum, Michel W.; Kalra, Vibha (JOURNAL OF MATERIALS CHEMISTRY A, 2023)
Potassium-sulfur cells have garnered a lot of interest in grid storage chemistry due to the high abundance of both elements and hence their low cost. However, their development is hindered by the polysulfide shuttle effect and their dependency on electrolytes with limited commercial viability. The inability to use carbonate electrolytes is due to the irreversible reaction between it and PS, rendering the cell useless in the first few cycles. Here we expand our use of monoclinic & gamma;-sulfur in carbon nanofibers (& gamma;S-CNFs) to the potassium-sulfur, K-S, chemistry. Herein we show that using & gamma;-S enables the cells to run for 500 cycles at & SIM;900 mA h g(-1) in commercial carbonate electrolytes. We further attempt to understand the role of & gamma;S-CNFs in K-S cells with electrochemical characterization and postmortem spectroscopy. As far as we are aware this is the first application of & gamma;-S in K-S cells. Its outstanding performance should lead to new avenues for the development of this promising chemistry.

Photo-stable, 1D-nanofilaments TiO2-based lepidocrocite for photocatalytic hydrogen production in water-methanol mixtures - Badr, Hussein O.; Natu, Varun; Neatu, Stefan; Neatu, Florentina; Kuncser, Andrei; Rostas, Arpad M.; Racey, Matthew; Barsoum, Michel W.; Florea, Mihaela (Matter, 2023)
Water and sunlight are the cleanest, most renewable, and abundant resources on Earth. Developing inexpensive, scalable photocatalysts that are highly stable for hydrogen (H-2) production has long been a cherished dream of humanity. Herein, we report on one-dimensional lepidocrocite-based sub-nanofilaments (NFs), approximate to 5 x 7 & Aring;(2) in cross-section, that generate H-2 from 80:20 v/v water/methanol mixtures when illuminated by simulated sunlight. The NFs were stable in the mixtures for times >4,300 h, 300 h of which were under irradiation. Apparent quantum yields as high as 11.7% were obtained. Based on deuterated water results, we conclude that water is the H-2 source. Further, no carbon dioxide (CO2) due to photocatalytic degradation of methanol was detected. Therefore, the NFs have strong green credentials and lucrative economic prospects for large scale up. We expect these NFs will lead to new lines for developing cheap and ultra-stable materials to produce H-2 photochemically for a long time.

Ultrafast spectroscopy of plasmons and free carriers in 2D MXenes - Colin-Ulloa, Erika; Fitzgerald, Andrew; Montazeri, Kiana; Mann, Javery; Natu, Varun; Ngo, Ken; Uzarski, Joshua; Barsoum, Michel W.; Titova, Lyubov V. (Advanced Materials, 2023)
2D MXenes have diverse and chemically tunable optical properties that arise from an interplay between free carriers, interband transitions, and plasmon resonances. The nature of photoexcitations and their dynamics in three different members of the MXene family, Ti3C2, Mo2Ti2C3, and Nb2C, are investigated using two complementary pump-probe techniques, transient optical absorption, and time-resolved terahertz (THz) spectroscopy. Measurements reveal pronounced plasmonic effects in the visible and near-IR in all three. Optical excitation, with either 400 or 800 nm pulses, results in a rapid increase in lattice temperature, evidenced by a pronounced broadening of the plasmon mode that presents as a plasmon bleach in transient absorption measurements. Observed kinetics of plasmon bleach recovery provide a means to monitor lattice cooling. Remarkably slow cooling, proceeding over hundreds of picoseconds to nanoseconds time scales, implies MXenes have low thermal conductivities. The slowest recovery kinetics are observed in the MXene with the highest free carrier density, viz. Ti3C2, that supports phonon scattering by free carriers as a possible mechanism limiting thermal conductivity. These new insights into photoexcitation dynamics can facilitate their applications in photothermal solar energy conversion, plasmonic devices, and even photothermal therapy and drug delivery.
Keywords: 2D properties; MXenes; Optical properties; plasmons; ultrafast spectroscopy